Goŋ Gurtha: Enacting response-abilities as situated co-becoming. (August 2019) - Country, Bawaka; Suchet-Pearson, Sandie; Wright, Sarah; Lloyd, Kate; Tofa, Matalena; Sweeney, Jill; Burarrwanga, Laklak; Ganambarr, Ritjilili; Ganambarr-Stubbs, Merrkiyawuy; Ganambarr, Banbapuy; Maymuru, Djawundil
In this paper, we engage with the Goŋ Gurtha songspiral, shared on/by/with/as Bawaka Country in Yolŋu Northeast Arnhem Land, Australia, to provide a basis for re-thinking responsibility in the context of ongoing Eurocentric colonising processes. Goŋ Gurtha encourages us to consider two key aspects of responsibility – response and ability. We argue that Yolŋu relational ontologies conceive response-abilities as requiring an ability to pay close and careful attention as part of more-than-human worlds, and an imperative to respond as part of these worlds. As such, rather than being responsible to or for others, we seek to respond as, emphasising our emergent co-becoming in more-than-human, situated, ethical ways. Goŋ Gurtha guides the paper through four aspects of these response-abilities: response-abilities as songspirals; response-abilities as continuity; response-abilities as academics and response-abilities beyond Bawaka. In doing so, we understand response-abilities as more-than-human co-becomings enacted in contingent ways that none-the-less need to be grounded in deep obligations of more-than-human kinship.